KNOWLEDGE, ATTITUDE, AND PRACTICE OF MARRIED FEMALE REGARDING BREAST CANCER PREVENTION AT A RURAL COMMUNITY, LAHORE - FATIMA , N; FIRDOS , U; SHAHEEN , R; NIAZ , F; KASHIF , M; ARSHAD , F; ZAFAR , M (Biological and Clinical Sciences Research Journal, 2023)
This study was conducted in a rural community to study the status of knowledge, attitude, and practice of breast self-examination among married females above 30. Breasts are crucial in defining the female body’s special function. One should have a brief idea of what is normal for the breast and not. The reason for conducting this study was to enable women to know the facts and causes of breast cancer and amputation in later stages to stimulate the women of the area to seek proper medical attention when needed. To identify married females’ knowledge, attitudes, and practices regarding breast cancer prevention in a rural community, Lahore. A cross-sectional study was conducted in a rural community. For this purpose, a simple random sampling technique was utilized for participant recruitment. A sample size of 80 was calculated for predicted event frequency. The researchers in the community administered the questionnaire. The data was evaluated using SPSS Statistical Software. And presented as frequency and percentage. Eighty females were selected from the community, and an adaptive, closed-ended, self-administered questionnaire was used to determine the knowledge, attitude, and practice of BSE in the community. The majority of the women were literate. The study revealed that among the 68.8% of females who have heard about breast self-examination, 95% of females think that breast self-examination is necessary. 88.8% of females think breast self-examination helps in the early detection of breast cancer. 65% of females know that breast self-examination should be performed once a month and 58.8 % know how to perform breast self-examination correctly. 62.5% of females are fully aware of its benefits. 52.5% of females know that breast self-examination is performed on the arm and upper chest areas. 76.3% don’t have a family history of breast cancer. 61.3% of females think that if there is no history of breast cancer, there is no need to practice breast self-examination. 92.5% of females know that breast self-examination is a good practice for all women must be taught. The study’s result was that the community’s knowledge was good. The efforts of the health department and the collaboration of media groups can further increase it.